Study on the global and spatial pulsation frequencies of rectangular syngas jet fire with different aspect ratios. (15th December 2022) - Zhao, Kun; Li, Situo; Lin, Ziming; Tang, Zhenhua; Qian, Jianan; Wang, Hua; Cui, Tong; Wang, Zhirong
Highlights: Rectangular syngas jet fires with different aspect ratios were studied. Global and spatial pulsation frequencies were obtained based on the FFT method. A transition of local dominant frequency from natural frequency to subharmonic frequency occurs at R i z ≈ 1 . The non-axisymmetrical development of the buoyant-induced outer vortices enhances the instability of rectangular jet flame. Abstract: Flame pulsation is a significant feature for both laminar and turbulent jet fires. In this study, the pulsation behaviors and the dominating mechanism of rectangular jet fires were explored. A series of experiments were conducted on the rectangular syngas jet fires with fuel flow rates ranging from 5 L/min to 45 L/min and aspect ratios ranging from 2 to 8. Both the global and spatial pulsation frequencies of syngas jet flame were obtained based on the time variations of image correlation coefficient and flame width. The local pulsation frequency of jet flame near the nozzle exit, which is defined as the natural frequency, increases slightly with the fuel flow rate due to the enhanced interaction of the inner vortex with the flame sheet and outer vortices. A transition from natural pulsation to subharmonic pulsation was found to happen when the local Richardson number ( Ri Z ) of the jet flame is close to 1. The global pulsation frequency is dominated by the natural frequency at the nozzle exit for Q f < 20 L/min, however, the subharmonic frequency for higher fuel flow rates. Non-axisymmetrical development of buoyancy-induced instability is considered to play a significant role in the rectangular jet fire, leading to the varied spatial pulsation frequency and the elongated flame height at side edges. In addition, the dimensionless global pulsation frequency ( St ) was found to correlate well with the Froude number ( Fr ) at the nozzle exit, St = 0.42 ( 1 / F r ) 0.46 for Fr > 10 and St = 0.40 ( 1 / F r ) 0.56 for Fr < 10.